PENTINGNYA PENGGUNAAN PENDEKATAN MULTIMODAL DALAM PEMBELAJARAN - Taufiq Akbar Al Fajri (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2020)
Nowadays globalization and rapid technological developments able to explained all means of meaning under the theory of multimodality. Multimodal is any source of verbal and visual semiotics that can be used to realize the type and level of dialogical engagement in a text of multimodal approach which is important in learning. The multimodal approach aims to develop students into readers and creator of multimodal text by drawing attention to various sources in making meaning in the text, as well as the ways in which a specific choice works to achieve the desired communicative goals. In addition, multimodal approaches help to meet diversity, ensuring inclusiveness that encourages intellectual quality and enables students to experience a vast learning experience. With a multimodal approach, students can choose for themselves the object of learning, or representation, which best suits their capital preferences based on their dominant learning style. Thus, enabling educators / teachers to meet the needs of different learners in a language learning environment.